Community Structure of Dragonfly (Ordo: Odonata) in Natural Forest and Tourist Sites Petungkriyono Forest, Central Java, Indonesia - Nur Apriatun Nafisah; R.C.Hidayat Soesilohadi (Universitas Gadjah Mada, 2021)
Petungkriyono forest is a tropical rainforest with high biodiversity. The increasing tourism activities in Petungkriyono lead to land conversion. Dragonfly (order Odonata) is a good bioindicator for aquatic and terrestrial. This study aimed to compare the community structure of Odonata in natural forests and tourist sites. The method of collecting imago Odonata was done by direct searching, samples were captured using sweep netting. The results showed that the dragonflies found in all locations consisted of the same family, 2 families (Gomphidae and Libellulidae) from the suborder Anisoptera and 6 families (Calopterygidae, Chlorocyphidae, Coenagrionidae, Euphaidae Platycnemididae, and Platystictidae) from the suborder Zygoptera. The total species of dragonflies found in Sokokembang were 15 species with a total of 293 individuals, Tirta Muncar 13 species of 287 individuals, Karanggondang 17 species of 276 individuals, and Curug Lawe 14 species of 242 individuals. The highest relative abundance of individuals was in the natural forest of Sokokembang is Drepanosticta spatulifera (26.28%) and in Karanggondang Vestalis luctuosa (24.64%), while in the tourist forests of Tirta Muncar and Curug Lawe were Euphaea variegata (34.84% and 28.51 %). The structure of the Odonata community is based on the Shannon-Wiener diversity index in the natural forests of Sokokembang (2.18) and Karanggondang (2.21) at the tourist sites of Tirta Muncar (1.84) and Curug Lawe (2.11). The results showed that the structure of the Odonata community based on the level of the diversity index value, evenness index, and dominance index in natural forests and tourist sites in Petungkriyono forest was not significantly different.